Effect of Needle Exchange Program on Maternal Hepatitis C Virus Prevalence - Rossi, Robert M.; Brady, Matthew J.; Hall, Eric S.; Warshak, Carri R. (American Journal of Perinatology, 2020)
Objective This study aimed to quantify the prevalence of maternal hepatitis C virus (HCV) before and after implementation of the needle exchange program (NEP) in Scioto County, Ohio.Study Design We conducted a population-based retrospective cohort study of all live births in Ohio (2006–2015). Frequency of maternal HCV was compared before (2006–2011) and after (2012–2015) the implementation of an NEP (2011) in Portsmouth, Ohio (Scioto County). Trends in maternal HCV prevalence in neighboring counties both physically adjacent and regional to Scioto County were also evaluated before and after NEP implementation.Results During the study period, there were 7,069 reported cases of maternal HCV infection at the time of delivery among 1,463,506 (0.5%) live births in Ohio. The rate of maternal HCV infection increased 137% in Scioto County between 2006 and 2011. After initiation of the NEP in Portsmouth, Ohio, in 2011, the rate of increase in the following 4 years (2012–2015) was 12%. The rate of increase in maternal HCV declined precipitously in counties physically adjacent to Scioto County, whereas regional counties continued to have substantial increases in maternal HCV.Conclusion Rate of maternal HCV infection increased 137% versus 12% (rate difference: 125%) between pre- and post-NEP implementation time periods in Scioto County.
Keywords: needle exchange; hepatitis C infection; maternal HCV